MedReach: building an Area Health Education Center medical information outreach system for Northwest Ohio - Steiner, Victoria (Medical Library Association, 2002)
In collaboration with regional partners in northwest Ohio, the Area Health Education Center (AHEC) program at the Medical College of Ohio (MCO) at Toledo is reaching out to underserved areas, helping to provide educational opportunities to health care professionals in these communities. This paper describes the development of MedReach, a medical information outreach system that connects regional AHEC sites to MCO via the Internet. MedReach provides physicians and other health care professionals access and support to search computerized textbooks and databases for current information on medical diagnoses, treatments, and research. A unique aspect of the MedReach project is that users are able to receive personal help with information retrieval by calling or emailing MCO's outreach librarian. Periodically, the AHEC program and the Mulford Library at MCO also sponsor an educational program, titled “Medical Applications of Computers,” for regional practitioners. Current feedback on both the medical information outreach system and the educational program has been positive.